HUBUNGAN PREEKLAMSIA DENGAN KONDISI BAYI YANG DILAHIRKAN SECARA SECTIO CAESAREA DI RSUD DR. MOEWARDI SURAKARTA - Ambarwati, Winarsih Nur; Irdawati, Irdawati (Universitas Muhammadiyah Surakarta, 2009)
Preeclampsia is major cause of maternal mortality in developed and developing countries. It is also a major cause of perinatal morbidity and mortality. Preeclampsia complicates almost 10 percent of all pregnancies, and the incidence is higher if the women are nulliparous. Perinatal outcome is strongly influenced by gestational age. The main impact on the fetus is undernutrition as a result of utero-placental vascular insufficiency, which leads to growth retardation, low birth weight, asfiksia, premature. Fetal health as well as its weight are highly compromised, leading to various degrees of fetal morbidity, and fetal damage may be such as to cause fetal death. This research was a documental study. The population is women pregnancy with preeclampsia at Dr.Moewardi Hospital in Surakarta. The sampling method was consecutive sampling. The analysis of variable used were Chi Square test. The results of this study show preeclampsia have siqnifican association with asfiksia neonatorum and baby birth weigt and premature birth.